Penyuluhan Kesehatan Reproduksi dalam Peningkatan Pengetahuan dan Sikap Remaja Mengenai Seksual Pranikah: Quasi Experimental - Ririn R Lamading; Levana Sondakh; Dwi Nur Octaviani Katili (Window of Midwifery Journal, 2026)
Premarital sexuality among adolescents is a significant issue that significantly impacts the reproductive health, psychology, and social well-being of young girls. The research aimed to assess the effect of reproductive health education on improving knowledge and changing attitudes among female students at SMK Negeri 1 Limboto. The study utilized a quasi-experimental design with a pre-post test control group design, a population of 84 people, and involved a sample of 32 students divided into 16 intervention and 16 control groups. The results of the Mann-Whitney test showed a p-value of 0,000 for knowledge, which was less than p < 0,05, indicating a significant difference in the average scores of the intervention group regarding the increase in knowledge. Similarly, for attitudes, there was a significant difference (p = 0,000), also less than p < 0,05, in both the knowledge and attitude groups. In conclusion, the study found that reproductive health education had a significant impact on the knowledge and attitudes of adolescent girls about premarital sexuality at SMK Negeri 1 Limboto